Average phenotype but not plasticity in two metabolic hormones covary in wild female bonobos (Pan paniscus) - Sonnweber, Ruth; Hohmann, Gottfried; Stevens, Jeroen M. G.; Deschner, Tobias; Fruth, Barbara; Fiedler, Anna-Lena; Nurmi, Niina O.; Behringer, Verena (Frontiers in Ecology and Evolution, 2023)
Each individual is equipped with a distinct genetic disposition and ontogenetic history and experiences environmental conditions in a unique way. Consequently, individuals vary in terms of phenotype regarding their responses to internal and external conditions. By modulating hormone secretion, an individual reacts to changing conditions, thus maintaining homeostasis. Cortisol and triiodothyronine (T3) are involved in mediating energy homeostasis. The secretion of metabolic hormones enables individuals to respond flexibly to internal and external conditions. However, this flexibility may be constrained by tradeoffs between average hormone levels and the degree of hormonal plasticity and the impact of the HPA axis on T3 secretion and effects. Like many other species, bonobos (Pan paniscus) are confronted with rapid ecological and climatic perturbations, resulting in challenges to energetic homeostasis. Due to their limited genetic diversity, K-strategist and stenoecious species characteristics, they are predicted to have limited potential for adaptation. Therefore, it is important to quantify individual cortisol and T3 reaction norms and examine their relationship with each other to understand the level of flexibility of metabolic hormone phenotypes. Using a multivariate random slope model, we found that diurnal urinary excretion patterns of cortisol and T3 in wild female bonobos have (i) no relationship between average phenotype and plasticity within the reaction norms of both hormones. (ii) We also found a negative correlation between the intercepts of the two metabolic hormones, but (iii) no relationship between their slopes. (iv) Standard deviations of cortisol and T3 intercepts and slopes between females indicate little variation among females. Our data show that plasticity within and between the two metabolic hormones is not related to overall low or high hormone levels, but there is a linear negative relationship between cortisol and T3 average phenotypes. Thus, individuals with high average cortisol levels, investing in restoring energy depots, have low average T3 levels, reducing energy expenditure, and vice versa. From this we conclude that the plasticity of diurnal hormone excretion is not affected by average metabolic hormone phenotypes. Evaluations of cortisol and T3 plasticity along ecological gradients can enhance our understanding of the adaptive potential of a given species to environmental changes.